Icetexane Diterpenoids from Perovskia atriplicifolia - Jiang, Zhi-Yong; Yu, Yi-Jiang; Huang, Chao-Guan; Huang, Xiang-Zhong; Hu, Qiu-Fen; Yang, Guang-Yu; Wang, Hong-Bin; Zhang, Xiang-Yu; Li, Gan-Peng (Planta Medica, 2015)
Five new icetexane diterpenoids, namely, perovskatones B–D (1, 3, 4), 1α-hydroxybrussonol (2), and 1α-hydroxypisiferanol (5), were isolated from Perovskia atriplicifolia, together with a new natural product (6) and two known compounds, przewalskin E (7) and brussonol (8). The structures of the new compounds were elucidated by detailed analyses of their MS, IR, 1D, and 2D NMR data. Compounds 1–8 were assayed for their inhibitory hepatitis B virus activities in the HepG 2.2.15 cell line. The results suggested that compounds 1 and 2 possessed noticeable anti-hepatitis B virus activity in vitro, suppressing the replication of hepatitis B virus DNA with selectivity index values of 154.3 and 137.7, respectively.
Keywords: Perovskia atriplicifolia; Lamiaceae; icetexane diterpenoids; anti-HBV activity